IMPLEMENTATION OF THE ISLAMIC BOARDING SCHOOL CURRICULUM IN FORMING THE - Rawasiyah, Rawasiyah; Imami, Agus Sulthoni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines the implementation of the pesantren curriculum at the Nurul Jadid Islamic Boarding School, especially in the Az-Zainiyah region, in shaping the social and spiritual character of students. The pesantren curriculum implemented in this pesantren shows a comprehensive and holistic approach, integrating religious education with the formation of social character through social activities such as community service and community service. Religious learning does not only focus on theological aspects, but also instills social values such as cooperation, empathy, and responsibility, which in turn strengthens the spiritual character of students. In addition, the pesantren curriculum also pays attention to the development of practical skills that support the social life of students, such as leadership, communication, and time management. The integration of social and spiritual characters has proven effective in producing students who have noble morals, are sensitive to social needs, and have a strong spiritual closeness to God. Despite several challenges, such as limited resources and difficulties in connecting theory with practice, Nurul Jadid Islamic Boarding School has succeeded in creating an environment that supports the formation of character as a whole. By strengthening the evaluation system and utilizing technology, this pesantren has great potential to continue to develop its curriculum and produce students who excel in religious knowledge and play an active role in the social and spiritual development of the community.